Identification of saprahan values as formers of gifted students empathy in high school students in pontianak - Hastiani Hastiani; Rezki Hariko (Universitas Negeri Padang, 2019)
Gifted students tend to have too perfectionistic social skills, want others to be in accordance with the desired logic, comfortable interacting with students with homogeneous characteristics. This tendency can be modified by school counselors through the integration of the values of Saprahan local wisdom into guidance and counseling services. The values contained in Saprahan are used as the formation of students' empathy skills. Thus, gifted students have concern for other colleagues, can interact well with students of various characters, accept the shortcomings of other friends, embrace and help other friends, be polite in communicating, and not demean other friends.